2023
DOI: 10.1039/d3tc01244a
|View full text |Cite
|
Sign up to set email alerts
|

High-performing TiO2 flower-like nanostructures based on flexible MWCNTs for dual-band terahertz absorption

Guruvandra Singh,
Subhash Nimanpure,
Nityananda Acharyya
et al.

Abstract: In the age of science and technology, the nanostructure plays a vital role for development of devices based on electronics and photonics. In this research work, we fabricated the TiO2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Upon examining figure 8(a), it became apparent that the THz signals exhibited a decrease in the amplitude of roughly 54% compared to the reference signal, along with a time delay in the electric field profile of the sample by ∆t = 2.73 ps. Calculations of the absorption coefficient along with transmission and refractive indexes were performed following the existing literature [26,47].…”
Section: Thz-tdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon examining figure 8(a), it became apparent that the THz signals exhibited a decrease in the amplitude of roughly 54% compared to the reference signal, along with a time delay in the electric field profile of the sample by ∆t = 2.73 ps. Calculations of the absorption coefficient along with transmission and refractive indexes were performed following the existing literature [26,47].…”
Section: Thz-tdsmentioning
confidence: 99%
“…Li and Cheng have introduced an adaptable dual-band terahertz ideal metamaterial absorber [25]. Singh et al investigated the dual band terahertz absorption TiO 2 nanostructure and demonstrated that it provides a means to improve the tunable detection within the terahertz frequency range [26]. Yet, the practical utility of single-band and dual-band absorption remains restricted in numerous applications, necessitating a device with broadband/multiband absorption capabilities.…”
Section: Introductionmentioning
confidence: 99%